Elevational microbial β diversity and community assembly processes in subarctic ponds - Teittinen, Anette; Wang, Jianjun; Soininen, Janne (Wiley Blackwell, 2024)
Knowledge about elevational β diversity patterns and processes is limited for microorganisms, especially in sensitive aquatic ecosystems at high latitudes. Our aim is to investigate elevational β diversity patterns and underlying assembly processes for three biofilm microbial groups in subarctic freshwater ponds. We sampled 89 ponds covering an elevational gradient from 10 to 1038 m above sea level in subarctic Finland and Norway. The microbial groups studied included benthic diatoms, cyanobacteria, and bacteria (i.e., bacteria other than cyanobacteria). We expected to find elevational distance decay in community similarity, driven primarily by variation in the local environment. We further tested whether the level of β diversity decreased towards higher elevations, and whether the relative influence of deterministic and stochastic processes on community assembly changed along the elevational gradient, with increasing effect of deterministic processes at higher elevations under more extreme environmental conditions. As statistical methods, we used generalised dissimilarity modelling, Mantel tests, and a null model with Raup–Crick dissimilarities. For all microbial groups, community dissimilarities increased with increasing environmental or elevational distances. The pure effects of environment were significant for all groups, and pH was the most important variable affecting community dissimilarities. Mean community dissimilarities generally decreased with elevation for all microbial groups. The communities were influenced by both deterministic and stochastic processes, the former of which was stronger towards higher elevations. The influence of deterministic processes was strongest for bacteria. Generally, the communities under deterministic control were more similar to each other than expected by chance. Elevational β diversity patterns of subarctic pond microorganisms primarily reflected environmental effects, showing decreasing β diversity towards high elevations owing to stronger environmental filtering. The ...